Operando Investigation of Ag‐Decorated Cu2O Nanocube Catalysts with Enhanced CO2 Electroreduction toward Liquid Products. Issue 13 (22nd February 2021) - Herzog, Antonia; Bergmann, Arno; Jeon, Hyo Sang; Timoshenko, Janis; Kühl, Stefanie; Rettenmaier, Clara; Lopez Luna, Mauricio; Haase, Felix T.; Roldan Cuenya, Beatriz
Abstract: Direct conversion of carbon dioxide into multicarbon liquid fuels by the CO2 electrochemical reduction reaction (CO2 RR) can contribute to the decarbonization of the global economy. Here, well‐defined Cu2 O nanocubes (NCs, 35 nm) uniformly covered with Ag nanoparticles (5 nm) were synthesized. When compared to bare Cu2 O NCs, the catalyst with 5 at % Ag on Cu2 O NCs displayed a two‐fold increase in the Faradaic efficiency for C2+ liquid products (30 % at −1.0 VRHE ), including ethanol, 1‐propanol, and acetaldehyde, while formate and hydrogen were suppressed. Operando X‐ray absorption spectroscopy revealed the partial reduction of Cu2 O during CO2 RR, accompanied by a reaction‐driven redispersion of Ag on the CuOx  NCs. Data from operando surface‐enhanced Raman spectroscopy further uncovered significant variations in the CO binding to Cu, which were assigned to Ag−Cu sites formed during CO2 RR that appear crucial for the C−C coupling and the enhanced yield of liquid products. Abstract : Cu2 O nanocubes showed a remarkable increase (30 %) in the Faradaic efficiency for C2+ liquid products after the decoration with Ag nanoparticles. Operando spectroscopy revealed a reaction‐driven redispersion of Ag on CuO x as well as a certain Cu–Ag miscibility. These changes were coupled with significant variations in the binding of CO to Cu that favored the enhancement of the liquid product yields.